Prevalence of Dermatophytic Infection and the Spectrum of Dermatophytes in Patients Attending a Tertiary Hospital in Addis Ababa, Ethiopia - Gebreabiezgi Teklebirhan; Adane Bitew (International Journal of Microbiology)
Background. Dermatophytosis is common worldwide and continues to increase. Objective. This study was undertaken to determine the prevalence of dermatophytosis and the spectrum of ringworm fungi in patients attending a tertiary hospital. Methods. Samples were collected from 305 patients. A portion of each sample was examined microscopically and the remaining portion of each sample was cultured onto plates of Sabouraud’s dextrose agar containing chloramphenicol with and without cycloheximide. Dermatophyte isolates were identified by studying macroscopic and microscopic characteristics of their colonies. Result. Of 305 samples, fungi were detected in 166 (54.4%) by KOH of which 95 were dermatophytes while 242 (79.4%) samples were culture positive of which 130 isolates were dermatophytes. Among dermatophyte isolates T. violaceum was the most common (37.7%) cause of infection. Tinea unguium was the predominant clinical manifestation accounting for 51.1% of the cases. Patients with age group 25–44 and 45–64 years were more affected. T. violaceum was the most common pathogen in tinea unguium and tinea capitis, whereas T. mentagrophytes was the most common pathogen in tinea pedis. Conclusion. Further intensive epidemiological studies of ring worm fungus induced dermatophytosis which have public health significance are needed.